Estudio histórico analítico del hurto de la Custodia de Riobamba y sus consecuencias en el patrimonio religioso-cultural - Lema Revelo, Jhoel Mesias (2021)
The theft of the Custody of Riobamba is one of the most important religious, social, and cultural events that occurred in the city during this century. It mainly affected the devout Catholic community. The objective of this research was to identify the consequences generated by the theft of the Custody of Riobamba in the cultural-religious heritage of the city; for this, an essential, non-experimental investigation was carried out with a descriptive and explanatory design that included a sample of 537 people among religious leaders, museum workers, and devout Catholics in general. In the respondents' opinion, the top results include that the majority of those surveyed considered causes that favored the theft, highlighting the economic causes and the museum's inadequate security. 58.10% agreed in stating that the Custody's theft did not affect the religious sentiment of the Catholics in Riobamba; however, they did consider that it generated economic damage (62.06%) and the socio-cultural heritage (74.31%). It is concluded that the theft of the Custody of Riobamba, despite being a reprehensible and unacceptable fact, did not influence religious sentiment but did have economic repercussions and the city's general socio-cultural heritage when one of its most relevant works was lost.